Impact of Sexual Abuse on Psychological Well-Being Among Senior High School Students in Northern Ghana - Salma, M (University of Ghana, 2014)
Child sexual abuse occurs throughout the world, although in most sub- Saharan countries there has been little research conducted on the problem and its psychological effects. Current research has established that a childhood history of sexual abuse is usually associated with a range of problem behaviors in childhood, adolescence and adulthood. Firstly, this study seeks to document the relationship between childhood sexual abuse and psychological wellbeing. Secondly, this study seeks to investigate the relationship between the forms of childhood sexual abuse and the types of perpetrators on psychological well-being. It further seeks to explore the moderating role of family relationships in the ensuing psychological sequelae following the experience of CSA. 380 Senior High School students from the Northern region of Ghana were used for the study. Results from the analyses indicated that there was no difference between males and females experience of CSA on psychological wellbeing. Results showed those students who experienced both forms of CSA (contact and non-contact) reported significantly less psychological wellbeing than students who experienced no CSA or only one form of CSA. Results further indicated that students who have experienced actual sex perpetrated by family members experienced less psychological well-being than students who experienced actual sex perpetrated by others. This means that sex perpetuated by family members have serious negative impact on victims. Finally it was observed that physical abuse and family relationships accounted for 24% and 13% of the variance in psychological distress respectively, indicating a significant impact of both on psychological distress. Implications for clinical practice and recommendations for future research are discussed.
Thesis (MPhil)- University of Ghana,2014